A cross sectional study of alcohol consumption and risk factors - R Dinesh Kumar; J Kalaiselvi; Siva S (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
Introduction : Alcohol consumption is an important contributor to the global burden of different disease such as stroke, sleep apnea, pancreatitis, diabetes mellitus, CAD and so on. Urban populations are having greater risk of getting the alcohol induced disease. Objective: A cross sectional study of alcohol consumption associated with risk of different disease. To inspect the correlation between alcohol intake and risk on different disease in men and women based on their age group and which leads to other diseased condition. Methods: A descriptive cross sectional survey was conducted involving 100 adults at 18 years of age or above who were recruited with cluster random sampling. Demographic data and risk factors were determined by taking history, physical examination and laboratory test.  Result: Studies shows that alcohol consumption increases the risk factor for those diseased condition i.e., it increases the risk on stroke, hypertension, coronary artery disease, Type 2 diabetes, life style. Results from our quantitative meta analysis showed that drinkers with average intake of less than 30 g/day and no episodic heavy drinking had a lowest risk on above complication. Discussion: Comparing to the present study with the former research the prevalence of a number of risk factors can be seen in the present research. We found out different statistical pattern. Conclusion: These findings indicate that alcohol consumption from mild to moderate intake is a risk factor for different diseases.